2013
DOI: 10.1093/jnci/djt224
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Role of KIAA1199, a Novel Endoplasmic Reticulum Protein, in Cancer Cell Migration

Abstract: KIAA1199 serves as a novel cell migration-promoting gene and plays a critical role in maintaining cancer mesenchymal status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
142
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(158 citation statements)
references
References 38 publications
10
142
1
Order By: Relevance
“…Nevertheless, CEMIP has several features that are inconsistent with the notion that it is a hyaluronidase that functions in the extracellular space. For example, although CEMIP is a secreted protein with an N-terminal signal sequence (38), culture supernatants of CEMIP-transfected cells show little HA-degrading activity (16), and CEMIP is detected mainly intracellularly (16,17). Concerning the lack of activity in culture supernatant, Yoshida et al (16) reported that CEMIP-mediated HA degradation requires the participation of the clathrin-coated pit pathway, suggesting that CEMIP may function in intracellular compartments rather than in the extracellular space.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, CEMIP has several features that are inconsistent with the notion that it is a hyaluronidase that functions in the extracellular space. For example, although CEMIP is a secreted protein with an N-terminal signal sequence (38), culture supernatants of CEMIP-transfected cells show little HA-degrading activity (16), and CEMIP is detected mainly intracellularly (16,17). Concerning the lack of activity in culture supernatant, Yoshida et al (16) reported that CEMIP-mediated HA degradation requires the participation of the clathrin-coated pit pathway, suggesting that CEMIP may function in intracellular compartments rather than in the extracellular space.…”
Section: Discussionmentioning
confidence: 99%
“…Also noteworthy is that neither conditioned media of CEMIP-expressing cells nor recombinant CEMIP show HA-degrading activity. In addition, CEMIP is detected mainly inside the cells (16,17).…”
Section: Hyaluronic Acid (Ha)mentioning
confidence: 99%
“…For example, KIAA1199 was significantly downregulated by B-Raf or MEK inhibition. KIAA1199 emerges as a marker of poor prognosis in several tumor entities, including colorectal carcinoma, but has never been linked to BRAF mutations before (39,40,55). Its activity as a promoter of cell migration in noncolorectal carcinoma cell lines (55) fits well to the strong reduction of invasive behavior of Colo-205 cells with inhibition or knockdown of B-Raf V600E .…”
Section: V600ementioning
confidence: 97%
“…Silencing a novel endoplasmic reticulum protein KIAA1199 discovered earlier to induce cell migration in invasive cancers caused a reduction of 75% in cell migration and 80% in cell invasion [35]. Another KKU-M213 exosome protein, CD147, was reported to play important roles in hepatocellular carcinoma invasion and metastasis [36].…”
Section: Accepted Manuscriptmentioning
confidence: 99%